An evaluation of the factors that affect the health-related quality of life of children following myelosuppressive chemotherapy - Baggott, Christina R. (Springer-Verlag, 2010)
PURPOSE: The purposes of this study, in children who were assessed 1 week after the administration of myelosuppressive chemotherapy were: to compare the total and subscale scores on a generic measure of health-related quality of life (HRQOL) to normative data from healthy children and describe the relationships between demographic, clinical, and symptom characteristics of children with cancer and generic and disease-specific dimensions of HRQOL. METHODS: Patients (n = 61) were predominantly male (52.5%), minority (63.9%), and 14.7 years of age. Children completed the Memorial Symptom Assessment Scale for 10- to 18-year olds, the PedsQL™ Generic and Cancer Modules, and the Karnofsky Performance Status (KPS) scale 1 week after the start of a chemotherapy cycle. RESULTS: The mean number of symptoms per patient was 10.6. Compared with the normative sample, children with cancer reported significantly lower scores for the total scale and all of the subscales except emotional and social functioning. No significant differences were found between any demographic characteristics and total or subscale scores on the generic or disease-specific measures of HRQOL. Lower KPS scores were associated with poorer generic and disease-specific HRQOL scores. In addition, a higher number of symptoms was associated with poorer generic and disease-specific HRQOL scores. Finally, higher symptom distress scores were associated with poorer generic and disease-specific HRQOL scores. CONCLUSION: Among the demographic, clinical, and symptom characteristics studied, poorer functional status and higher symptom burden were associated with significant decreases in HRQOL in children who received myelosuppressive chemotherapy.